The Early Textual History of Lucretius' De rerum natura / [electronic resource] - Butterfield, David (Cambridge : Cambridge University Press, 2013)
This is the first detailed analysis of the fate of Lucretius' De rerum natura from its composition in the 50s BC to the creation of our earliest extant manuscripts during the Carolingian Age. Close investigation of the knowledge of Lucretius' poem among writers throughout the Roman and medieval world allows fresh insight into the work's readership and reception, and a clear assessment of the indirect tradition's value for editing the poem. The first extended analysis of the 170+ subject headings (capitula) that intersperse the text reveals the close engagement of its Roman readers. A fresh inspection and assignation of marginal hands in the poem's most important manuscript (the Oblongus) provides new evidence about the work of Carolingian correctors and offers the basis for a new Lucretian stemma codicum. Further clarification of the interrelationship of Lucretius' Renaissance manuscripts gives additional evidence of the poem's reception and circulation in fifteenth-century Italy.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).